2018
DOI: 10.12659/msm.911548
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Exercise on Serum Osteoprotegerin Levels and Insulin Resistance in Middle-Aged Women with Metabolic Syndrome

Abstract: BackgroundOsteoprotegerin (OPG) is a soluble glycoprotein that belongs to the tumor necrosis factor (TNF) receptor superfamily. OPG is mainly secreted by bone. The relationship between acute resistance training, serum OPG levels and metabolic syndrome, including insulin resistance, remains unclear. The purpose of this study was to determine the effect of resistance exercise on serum OPG levels and insulin resistance in middle-aged women with metabolic syndrome.Material/MethodsTwenty-four middle-aged women were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In the present analysis, we explored the potential effects of a structured lifestyle intervention on OPG and sRANKL serum concentrations and demonstrated that the MedD in combination with increased physical activity may be biomarker modulators. To the best of our knowledge, this is the first time that lifestyle intervention-based alterations in OPG and sRANKL serum Several studies propose that OPG can be increased directly through physical activity by the mechanism of mechanical bone stress [40,50,51]. While Ziegler et al showed that OPG concentrations increased immediately after an endurance exercise [27], Bergström et al found significantly elevated OPG levels after a structured 1-year endurance training [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present analysis, we explored the potential effects of a structured lifestyle intervention on OPG and sRANKL serum concentrations and demonstrated that the MedD in combination with increased physical activity may be biomarker modulators. To the best of our knowledge, this is the first time that lifestyle intervention-based alterations in OPG and sRANKL serum Several studies propose that OPG can be increased directly through physical activity by the mechanism of mechanical bone stress [40,50,51]. While Ziegler et al showed that OPG concentrations increased immediately after an endurance exercise [27], Bergström et al found significantly elevated OPG levels after a structured 1-year endurance training [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies propose that OPG can be increased directly through physical activity by the mechanism of mechanical bone stress [ 40 , 50 , 51 ]. While Ziegler et al showed that OPG concentrations increased immediately after an endurance exercise [ 27 ], Bergström et al found significantly elevated OPG levels after a structured 1-year endurance training [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results do not support the hypothesis that muscle mass gain (observed in LLRT) is a mediator of RT-induced reduction in these circulating inflammatory biomarkers. Although the increase in energy expenditure, insulin sensitivity (7), and improvement in endocrine function of skeletal muscle (increasing anti-inflammatory myokine production) (41) have been proposed as possible mechanisms of muscle mass gain-induced reduction in circulating proinflammatory biomarkers (46), these effects may occur acutely with RT and, therefore, separate from muscle mass gains (18,20,21,32,37,41). Thus, it seems that muscle mass gain is not a therapeutic target of RT for improving circulating proinflammatory biomarkers in PW.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, improving insulin sensitivity is beneficial to the cardiovascular health. Aerobic exercise can significantly improve insulin resistance and mitochondrial function, itself serving as an effective strategy for the treatment of metabolic syndrome 28 , 29 . Of note, the age, gender as well as exercise intensity should be considered when improving insulin resistance with exercise training.…”
Section: Exercise Reduces the Risk For Cvdsmentioning
confidence: 99%